Analisis keefektifan aplikasi keuangan online sebagai media pengelolaan keuangan di sektor Usaha Mikro Kecil Menengah (UMKM) - Ramadhani, Rafli; Trisnaningsih, Sri (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Technological developments that have entered the 4.0 era which emphasizes the pattern of the digital economy, artificial intelligence, big data, or known as the disruptive innovation phenomenon, cannot be denied that accounting records are also developing. This form of innovation in the recording model in the form of an online financial application will make it easier for MSME actors to record and find out what the final cash balance is. In this study, online financial applications which include the online financial applications of Bukukas and Buku Warung proved to be very useful in managing and assisting in the form of good financial management of business people, namely in terms of managing income, expenses, accounts payable and financial statements. In addition, it is more effective and efficient in terms of financial management time by using the online financial application.